TEACHING WRITING THROUGH THE WRITING PROCESS APPROACH - Novi Indriyani (Acceleration: Multidisciplinary Research Journal, 2024)
This research aims to further explore the impact of the writing process approach on students' writing skills and critical thinking abilities within the realm of English education. Qualitative data will be collected through surveys and assessments conducted among students who have been exposed to the written process approach in English education, and qualitative data will also be gathered through in-depth interviews with educators who have implemented this approach in their teaching practices. The findings of this research will provide valuable insights for educators, curriculum developers, and policymakers. The integration of both quantitative and qualitative results will allow for a comprehensive analysis of the impacts of implementing this approach on the field of language instruction. The results from this research highlight the value of student-centered pedagogies and iterative writing processes in cultivating a generation of adept communicators and analytical thinkers in an increasingly interconnected world.